A CONTENT ANALYSIS OF EUPHEMISM-FORMATION STRATEGIES IN EVRO DAILY NEWSPAPER - Mohammed, Fakhir Omar; Majeed, Suhayla H. (Humanities Journal of University of Zakho, 2018)
The current paper tries to answer the question: What are the most important strategies for forming euphemisms on the word and sentence levels in the Kurdish daily newspaper, Evro? In order to reach accurate findings and results, the researcher followed the methodological procedures of Content Analysis (hence CA) by Berelson (1952) and Krippendorff (2003). Adopting a modified version of Warren’s Model (1992) for the classification of euphemistic strategies, the data extracted from sample texts were processed and analyzed statistically via Excel sheets and SPSS software. The results obtained throughout this paper show that different euphemistic strategies within various topic clusters (i.e. politics, economy, death, religion, sports, etc.) manifest different percentages. On the word level, loan words show the highest percentage (40.3%) from among all other strategies. In contrast, euphemisms related to reduplication strategy have the lowest percentage (1.8%). With regard to other strategies, they are measured from high to low ranking, starting from understatement (24.4%) followed by remodeling (13.7%), acronyms (7.6%), overstatement (6.9%) and underspecification (5.4%). On the sentence level, the passive voice strategy shows the highest percentage (30.4%) from among all other strategies; however, euphemisms related to litotes strategy have the lowest percentage (6.7%). With regard to the other strategies, they start from metaphors (25.5%) followed by idioms (25.2%), and finally downtoners (12.1%). Finally, the use of euphemistic strategies in question was measured to test statistical differences between these strategies across specified semantic topic clusters, by means of a series of ANOVAs and multiple comparison correlations, that were programmed and output by SPSS software 17.0.